2018
DOI: 10.20944/preprints201810.0117.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endometrial Intracrinology: Oestrogens, Androgens and Endometrial Disorders

Abstract: Peripheral tissue metabolism of steroids (intracrinology) is now accepted as a key way in which tissues, such as the endometrium, can utilize inactive steroids present in the blood to respond to local physiological demands and ‘fine-tune’ the activation or inhibition of steroid hormone receptor-dependent processes. Expression of enzymes that play a critical role in activation and inactivation of bioactive oestrogens (E1, E2) and androgens (A4, T, DHT), as well as expression of steroid hormo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…To the best of our knowledge, no studies about endometrial DHEA conversion in androgens/estrogens are present in the literature. However, circulating DHEA and DHEA-S can be utilized as androgen/estrogen precursors by the human endometrium, and this conversion can be differently regulated in both normal and pathologic endometrium (Gibson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no studies about endometrial DHEA conversion in androgens/estrogens are present in the literature. However, circulating DHEA and DHEA-S can be utilized as androgen/estrogen precursors by the human endometrium, and this conversion can be differently regulated in both normal and pathologic endometrium (Gibson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sex steroid hormone biosynthesis. The availability of biologically active sex steroids within the endometrium is dependent on the action of local endometrial sex steroid-metabolizing enzymes 59 (fIg. 3).…”
Section: ();mentioning
confidence: 99%
“…62 ). Endometrial steroid hormone metabolism studies, which extend over nearly 50 years, initially demonstrated steroid sulfatase activity, and these were followed by studies concerning oxidative and reductive 17β-hydroxysteroid dehydrogenase (17β-HSD) activities 59 . These steroid-metabolizing enzymes are involved in endometrial steroid hormone (ligand) availability and thus are involved with modulation of the local endometrial hormone environment.…”
Section: Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that EDCs may affect fertility (8)(9)(10)(11) and the progression of some diseases like obesity, endometriosis and some cancers (8,12,13). The disruption of sex hormone homeostasis (14) has been associated with the risk of sex-specific cancers, including: breast and prostate cancers (15,16), and possibly endometrial and ovarian cancers (17,18). The incidence of colorectal cancer differs by sex (19), and accumulating epidemiologic evidence shows that exposure to certain female sex hormones is associated with a lower risk of colorectal cancer (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%